2007
DOI: 10.1111/j.1527-3466.2007.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐(p‐Amylcinnamoyl)anthranilic Acid (ACA): A Phospholipase A2 Inhibitor and TRP Channel Blocker

Abstract: Phospholipase A 2 enzymes display a superfamily of structurally different enzymes classified in at least nine subfamilies by biochemical and structural properties. N-(pamylcinnamoyl)anthranilic acid commonly referred to as ACA is often used as a broadspectrum inhibitor for the characterization of phospholipase A 2 -mediated pathways. Compounds like ACA and ACA-like structures have been described to block the receptor-induced release of arachidonic acid and subsequent signaling cascades in the pancreas and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 73 publications
0
47
2
1
Order By: Relevance
“…3, A-C). Ca 2ϩ release from the vacuole in response to hyperosmotic stress has been earlier shown to involve YVC1, a TRP channel (34) that could be a target of ACA (47). Indeed, the [Ca 2ϩ ] cyt transient we see in response to NaCl is attenuated in ACA-pretreated cells (supplemental Fig.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…3, A-C). Ca 2ϩ release from the vacuole in response to hyperosmotic stress has been earlier shown to involve YVC1, a TRP channel (34) that could be a target of ACA (47). Indeed, the [Ca 2ϩ ] cyt transient we see in response to NaCl is attenuated in ACA-pretreated cells (supplemental Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Identifying Candidate Signaling Intermediates That Regulate Salt Tolerance of K616-ACA2-ACA is reported to both inhibit phospholipase A2 and block TRP channels (47). ACA was preincubated with log phase cells of K601 and K616-ACA2 at sublethal doses (30 and 40 M), followed by an 18-h exposure to a range of NaCl (0 -1000 mM).…”
Section: Requirement Of Nhx1 For Survival Of K616-aca2-the Sequestratmentioning
confidence: 99%
“…For example, 2-aminoethoxy diphenyl borate was initially characterized as an antagonist of the inositol 1,4,5-triphosphate (InsP3) receptor (Maruyama et al, 1997) and more recently has been reported to inhibit several members of the TRPC and TRPM families, including TRPC1,3,5,6 and TRPM2,3,7,8 (for review see Ramsey et al, 2006). N-(p-amylcinnamoyl)anthranilic acid is a well-characterized phospholipase A 2 antagonist (Konrad et al, 1992;Harteneck et al, 2007), with minimal TRP channel targets, inhibiting only TRPC6, TRPM2, and TRPM8 (Harteneck et al, 2007). Importantly, CTZ has not been demonstrated to inhibit any TRP channels other than TRPM2, making this the most promising compound to proceed to in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…1A). Clotrimazole and ACA were previously shown to block heterologously expressed TRPM2 channels (20,21).…”
Section: Significancementioning
confidence: 99%